The Influence of Current Ratio, Debt to Equity Ratio, Return on Asset Ratio, and Return on Equity Ratio on Company Profit Growth During the Covid-19 Pandemic - Nur Alfarizzi, Ahmad; Sasongko, Noer (DINASTI RESEARCH, 2024)
This research aims to analyze the influence of the current ratio, debt to equity ratio, return on asset ratio, and return on equity ratio on the profit growth of manufacturing companies in the basic industrial and chemical sectors listed on the two Indonesian Stock Exchanges for the 2019-2022 period. The sampling technique used purposive sampling, so that 128 samples were obtained that met the research criteria. The analytical method used is multiple linear regression analysis. The results of this research show that the debt to equity ratio and return on equity ratio have an effect on company profit growth, while the current ratio and return on asset ratio have no effect on company profit growth.